From Counterpublic to the Mainstream: The New Black Press and the Public Sphere. (25th January 2023) - Bedingfield, Sid
ABSTRACT: This article explores an important development in mainstream U.S. journalism that has not received the attention it deserves. Since 2008, elite news and opinion outlets like the New York Times have placed Black advocacy journalists in positions where they can allocate resources, shape editorial decisions, and – in the tradition of the historical Black press – challenge long-standing narratives of the nation's racial history. Using concepts first developed by Black and feminist critics of Habermas's theory of democratic deliberation, this article contends this new Black press has shed its status as a "counterpublic" and is fighting to build a new consensus on racial justice from within the mainstream public sphere. The article contextualizes this effort by examining two critical junctures in the nation's history when the white, mainstream press helped reify racial narratives the new Black press is now struggling to dismantle. It also explores the backlash against the new Black press, and it raises questions about the functionality of the current networked public sphere.